Lysosomal dysfunction and impaired autophagy underlie the pathogenesis of amyloidogenic light chain‐mediated cardiotoxicity. Issue 5 (May 2015) - Guan, Jian; Mishra, Shikha; Qiu, Yiling; Shi, Jianru; Trudeau, Kyle; Las, Guy; Liesa, Marc; Shirihai, Orian S; Connors, Lawreen H; Seldin, David C; Falk, Rodney H; MacRae, Calum A; et al.
Abstract :